Quality improvement project to routinely identify sensory and eating challenges in childhood neurodevelopmental movement disorders - Tamsin Owen; Tammy Hedderly; Osman Malik; Sara Sopena; Sandra-Eve Bamigbade; Amanda K Ludlow (BMJ Open Quality)
Sensory, eating and mealtime (SEM) challenges are common among young people with neurodevelopmental movement disorders but are rarely assessed during initial clinical consultations. This quality improvement project aimed to evaluate the impact of routine SEM screening on identifying these challenges and improving documentation and follow-up in a specialist paediatric movement disorder clinic in England. Using the SHIFT-Evidence Framework and a Plan-Do-Study-Act approach, the project implemented and evaluated a series of interventions. In the ‘PLAN’ phase, clinicians participated in a workshop to raise awareness of SEM challenges and inform the development of screening questions to support routine SEM assessment. The ‘DO’ phase involved implementing routine SEM screening during a 3 month trial, supported by active measures such as project champions, weekly reminders and team discussions to encourage sustained practice. The ‘STUDY’ phase included analysis of assessment outcome letters from three time points (baseline, trial and outcome retention phases) to evaluate changes in documentation and the sustainability of improvements. In the ‘ACT’ phase, findings were shared with the team, resulting in improved signposting, targeted recommendations and ongoing collaborations with feeding clinics. Findings demonstrated increased documentation of SEM challenges in assessment letters, with mentions rising from 33% at baseline to 71.9% during the trial and 64.3% in the retention phase. However, actionable recommendations and interventions remained limited during the trial but showed improvement in the retention phase, where letters included more tailored guidance and specific advice for SEM challenges. This project highlights the prevalence of SEM challenges among young people with neurodevelopmental movement disorders and underscores the importance of routine SEM screening. Developing standardised assessment tools and protocols could further aid clinicians in identifying and addressing these challenges during initial assessments.